Controlling the half-step mode operation of the variable reluctance stepper motor by using Mamdani type of fuzzy logic controller - Mustafa A. Mhawesh; Ahmed S. Kashkool (Institute of Advanced Engineering and Science, 2022)
This paper proposed the step angle controlling of the half-step mode operation of the variable reluctance stepper motor (VRSM) by using Mamdani type of fuzzy logic controller (FLC). The MATLAB program was used to achieve the approach. The VRSM that was used in this paper has six stator poles and four rotor poles. The VRSM has three phases that represent the input variables and the step angle represents the output variable in the FLC in MATLAB. Membership functions were created for the input and output variables. The rules of the FLC were built in MATLAB. The theoretical step angles results of the VRSM were obtained by using mathematically equation while the practical results were obtained by using MATLAB. The obtained results are closer to the actual results depending on the comparison between the theoretical and practical readings. These results were written in table and were plotted in figure.